(5x+3-2)(8-2x+1)=

Simple and best practice solution for (5x+3-2)(8-2x+1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5x+3-2)(8-2x+1)= equation:


Simplifying
(5x + 3 + -2)(8 + -2x + 1) = 0

Reorder the terms:
(3 + -2 + 5x)(8 + -2x + 1) = 0

Combine like terms: 3 + -2 = 1
(1 + 5x)(8 + -2x + 1) = 0

Reorder the terms:
(1 + 5x)(8 + 1 + -2x) = 0

Combine like terms: 8 + 1 = 9
(1 + 5x)(9 + -2x) = 0

Multiply (1 + 5x) * (9 + -2x)
(1(9 + -2x) + 5x * (9 + -2x)) = 0
((9 * 1 + -2x * 1) + 5x * (9 + -2x)) = 0
((9 + -2x) + 5x * (9 + -2x)) = 0
(9 + -2x + (9 * 5x + -2x * 5x)) = 0
(9 + -2x + (45x + -10x2)) = 0

Combine like terms: -2x + 45x = 43x
(9 + 43x + -10x2) = 0

Solving
9 + 43x + -10x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(9 + -2x)(1 + 5x) = 0

Subproblem 1

Set the factor '(9 + -2x)' equal to zero and attempt to solve: Simplifying 9 + -2x = 0 Solving 9 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -2x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -2x = 0 + -9 -2x = 0 + -9 Combine like terms: 0 + -9 = -9 -2x = -9 Divide each side by '-2'. x = 4.5 Simplifying x = 4.5

Subproblem 2

Set the factor '(1 + 5x)' equal to zero and attempt to solve: Simplifying 1 + 5x = 0 Solving 1 + 5x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 5x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 5x = 0 + -1 5x = 0 + -1 Combine like terms: 0 + -1 = -1 5x = -1 Divide each side by '5'. x = -0.2 Simplifying x = -0.2

Solution

x = {4.5, -0.2}

See similar equations:

| 9-.333g=13 | | 2x^2+9x=5 | | .25f=8-3 | | 3(4x-3)+2x=89 | | .25f+3=8 | | 3(4x+3)=68 | | 2(x+5)-10=8 | | 4x-20=7x+14 | | 15m-2(3+5m)= | | 15x^2-50y+35=0 | | 2-(8p-q)-7(p+6)+4q= | | -8x+x^2=-12 | | x^2-x-20=0 | | 7(p+3)=7b-4 | | f(11)=1/2(11)+5 | | 9(s+7)-(7s+m)-9m= | | f(11)=2(11)+5 | | 9(7x+8)+3(x+-10)= | | 7x+9=-11x+12 | | 7x+9and=-11x+12 | | -(9q+7)+3(2q-5)= | | 8y-2=14y-3 | | 20-4(w+1)=9w-4(9+w) | | 3(s-5)-7(4s-7)= | | 2x+40=90 | | wx=-4 | | P=a+2 | | 9x-(-6x-6)=-24 | | -2-(6t+9)= | | y=6x+18 | | -510=-4+2x | | 11x+8=69 |

Equations solver categories